2021
DOI: 10.32615/ps.2021.046
|View full text |Cite
|
Sign up to set email alerts
|

Blue light dosage affects photosynthesis, chlorophyll, and antioxidant properties of Mesembryanthemum crystallinum

Abstract: yield of PSII photochemistry in the dark-adapted state; gs -stomatal conductance; LA -leaf area; LCP -light-compensation point; MDA -malondialdehyde content; PN -net photosynthetic rate; PNmaxlight-saturated net photosynthetic rate; RD -dark respiration rate; ФNA -quantum yield of nonphotochemical energy dissipation in PSI in the light-adapted state due to the acceptor-side limitation; ФND -quantum yield of nonphotochemical energy dissipation in PSI in the light-adapted state due to the donor-side limitation; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The quality and quantity of light can be manipulated to improve yield and the phytonutrient contents of leafy greens. Applying an appropriate LED spectral wavelength significantly increases antioxidant enzyme activity in plants [10], thereby enhancing cell defence systems and providing protection from oxidative damage. It is possible to optimize productivity and quality through the optimization of the lighting to align with the sensitivity curve of the photosensitive pigments in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The quality and quantity of light can be manipulated to improve yield and the phytonutrient contents of leafy greens. Applying an appropriate LED spectral wavelength significantly increases antioxidant enzyme activity in plants [10], thereby enhancing cell defence systems and providing protection from oxidative damage. It is possible to optimize productivity and quality through the optimization of the lighting to align with the sensitivity curve of the photosensitive pigments in plants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, constant illumination with monochromatic red light may result in plants with abnormal leaf structure and anatomy, as well as lower photosynthetic rates, compared to plants provided by a combination of red and blue light or composite white light (Hogewoning et al 2010). Plants exposed to monochromatic blue light for a long period may also be negatively affected, exhibiting impaired mesophyll conductance (Loreto et al 2009), and a lower photosynthetic rate (Kim et al 2004, Zhang et al 2021. Previous studies have demonstrated that a combination of different wavelengths of monochromatic light in the visible spectrum is needed for normal plant growth, development, and photosynthesis (Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%